The significance of detecting glucose transporter 1 and calretinin in serous effusions to differentiate between carcinoma cells and reactive mesothelial cells. Issue 7 (5th April 2021) - Lv, Ming; Cha, Na; Zou, Yu‐Feng; Leng, Ji‐Hong; Hao, Yan‐Yong; Wang, Shuai
Abstract: Background: The cytologic evaluation of serous effusions to distinguish malignant cells from reactive mesothelial cells (RMCs)was an enormous challenge. The purpose of this study was to investigate the diagnostic value of glucose transporter 1 (GLUT1) and calretinin (CR) in serous effusions of patients with malignant and in order to significantly ameliorate the diagnostic accuracy. Methods: The expressions of GLUT1 and CR were measured by streptavidin‐peroxidase (S‐P) immunocytochemical technique in serous effusions of 183 patients with malignant and in 95 patients with benign diseases. Results: The positive ratio of GLUT1 was 91.8% (168/183) in serous effusions from patients with malignant and 5.3% (5/95) in benign diseases, they had a significant difference ( P < .01). CR was expressed 89.5% (85/95) in benign diseases and 6.6% (12/183) in malignant, it also showed an important difference (P < 0.01). The combination of GLUT1 + CR revealed the best efficiency: the sensitivity and specificity were 100% and 98.9%, respectively. Conclusion: Immunocytochemical staining for GLUT1 and CR may be used as a complementary tool for the detection of malignant effusions and help to make a distinction between cancer cells and RMCs. The combination of GLUT1 and CR with immunocytochemistry stained can be achieved a higher diagnostic performance.